2020
DOI: 10.1038/s41467-019-13918-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histone deacetylation rescues phenotype in a mouse model of Birk-Barel intellectual disability syndrome

Abstract: Mutations in the actively expressed, maternal allele of the imprinted KCNK9 gene cause Birk-Barel intellectual disability syndrome (BBIDS). Using a BBIDS mouse model, we identify here a partial rescue of the BBIDS-like behavioral and neuronal phenotypes mediated via residual expression from the paternal Kcnk9 (Kcnk9 pat ) allele. We further demonstrate that the second-generation HDAC inhibitor CI-994 induces enhanced expression from the paternally silenced Kcnk9 allele and leads to a full rescue of the behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A possible explanation could be that D2R in the prefrontal cortex is not involved in recognition memory processes and CI-994 improving memory function in HAL treated aged mice may be through regulating histone acetylation at other genes that are associated with memory function or indirectly improved memory by decreasing drug induced side effects. Various studies have shown that histone modifications change at memory-related genes contribute to age and disease-related cognitive decline, and HDAC inhibitors can reverse such effects (Francis et al, 2009;Kilgore et al, 2010;Peleg et al, 2010;Graff et al, 2014;Yao et al, 2014;Benito et al, 2015;Cooper et al, 2020). Therefore, in future studies we plan to investigate whether HAL administration could affect the histone acetylation changes occurring at memory and synaptic plasticity-related genes in aged mice, then to determine whether HDAC inhibitors could mediate such effects.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation could be that D2R in the prefrontal cortex is not involved in recognition memory processes and CI-994 improving memory function in HAL treated aged mice may be through regulating histone acetylation at other genes that are associated with memory function or indirectly improved memory by decreasing drug induced side effects. Various studies have shown that histone modifications change at memory-related genes contribute to age and disease-related cognitive decline, and HDAC inhibitors can reverse such effects (Francis et al, 2009;Kilgore et al, 2010;Peleg et al, 2010;Graff et al, 2014;Yao et al, 2014;Benito et al, 2015;Cooper et al, 2020). Therefore, in future studies we plan to investigate whether HAL administration could affect the histone acetylation changes occurring at memory and synaptic plasticity-related genes in aged mice, then to determine whether HDAC inhibitors could mediate such effects.…”
Section: Discussionmentioning
confidence: 99%
“…KCNK9 is among a small number of paternally imprinted genes where only the maternal allele is expressed [ 3 ]. Recent mouse studies, however, have detected residual paternal expression in some brain regions [ 4 ]. KCNK9 imprinting syndrome (KIS), also known as Birk-Barel syndrome (MIM: 612292), is a rare genetic disorder caused by a genetic alteration of the maternal copy of KCNK9, first reported with the causal variant, p.(Gly236Arg) [ 5 ], and two subsequent variants of uncertain significance (VUS) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We focused on H3K27ac, a known marker of active enhancers that is enriched at activity-dependent regulatory elements after neuronal activation (30, 42, 52-54), correlates with gene transcription (30,55) and often co-occurs with H3K9ac, a marker of active promoters (56). Furthermore, in line with previous studies (15,25,57,58), we found that HDACi treatment increased global H3K27ac, alongside H3K9ac and H4K12ac as revealed by western blotting (Two-way ANOVA, F(3,60) = 22.47, P = 1.11e-13) (Supplemental Fig. 11).…”
Section: Hdaci Combined With Cfc Enriches H3k27ac At Genes Involved In Synaptic Communicationmentioning
confidence: 64%
“…To investigate the mechanisms by which systemic HDACi treatment enhances fear memory, we treated mice with the HDACi CI-994, before subjecting them to a subthreshold contextual fear conditioning (CFC) task, a modified Pavlovian conditioning paradigm that, alone, does not induce memory formation (21). CI-994 is a class I HDACi that selectively impedes HDACs 1-3 (22), promotes functional recovery after stroke (23), and that has shown promise against cognitive dysfunctions in preclinical animal models (15,24,25). When i.p.…”
Section: Systemic Hdaci Treatment Enhances Memory Consolidation After Subthreshold Contextual Fear Conditioningmentioning
confidence: 99%